Orientation of loci within the human major histocompatibility complex by chromosomal in situ hybridization. - Morton, C C (1984)
We have determined the localization and orientation of two genetic probes within the human major histocompatibility complex by chromosomal in situ hybridization. Our data indicate that a cloned genomic probe cross-hybridizing to HLA-A, -B, and -C heavy chain loci is homologous to sequences located on chromosome 6 at band p21.3 while a subclone of the genomic HLA-DR alpha-chain gene corresponding to the nonpolymorphic p34 protein is homologous to sequences in band 6p21.1. Our data suggest that this technique may permit the estimation of map distances between linked gene loci, assuming a uniform frequency of map units in the human genome. The relative positions of these genes was confirmed in a mother and son carrying a chromosome rearrangement involving 6p and 14p in which the sequences hybridizing to a DR alpha-chain genomic clone were found at the distal end of the 6p--chromosome [der(6)] while the sequences hybridizing to the HLA-A, -B, -C alpha-chain probe were found in the 14p+ chromosome [der(14)].